2009
DOI: 10.1051/forest/2008092
|View full text |Cite
|
Sign up to set email alerts
|

Un incendie modifie la configuration spatiale de la disponibilité des éléments nutritifs dans les sols de forêts de Pinus canariensis

Abstract: Keywords:forest wildfire / ionic exchange membrane / SADIE / soil nutrient availability / spatial heterogeneity Abstract • Soil resources are heterogeneously distributed in terrestrial plant communities. This heterogeneity is important because it determines the availability of local soil resources. A forest fire may change the spatial distribution of soil nutrients, affecting nutrition and survival of colonizing plants. However, specific information on the effects of ecosystem disturbance on the spatial distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 50 publications
(54 reference statements)
2
26
0
Order By: Relevance
“…In our study, the spatial heterogeneity of post-fire soil respiration increased immediately, which might have been caused by the multiple small patches of exposed mineral soil and the areas with unburned organic matter. As time elapses after fire, the organic horizon develops and the cover of feather moss increases (Rodríguez et al 2009); therefore, we expect that the spatial heterogeneity of soil respiration might decrease over time. Further study is required to determine whether the spatial heterogeneity in soil respiration declines with time after a fire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the spatial heterogeneity of post-fire soil respiration increased immediately, which might have been caused by the multiple small patches of exposed mineral soil and the areas with unburned organic matter. As time elapses after fire, the organic horizon develops and the cover of feather moss increases (Rodríguez et al 2009); therefore, we expect that the spatial heterogeneity of soil respiration might decrease over time. Further study is required to determine whether the spatial heterogeneity in soil respiration declines with time after a fire.…”
Section: Discussionmentioning
confidence: 99%
“…Boreal forest ecosystems at high latitudes are very sensitive to global climate change (Kelsey et al 2012) and are also fire-prone. They often experience highintensity forest fires that cause great uncertainties in estimates used to quantify the global carbon cycle (French et al 2004;Rodríguez et al 2009). The uncertainties are caused by variation in soil characteristics at high latitudes and by changes in the forest environment after fire disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, age 13 displayed even higher germination values than control areas. The recovery of nitrogen content in the long term may be masked or exceeded in importance by other stand conditions such as the modification of nutrients spatial heterogeneity (Rodríguez et al 2009). Consequently, the existence of suitable microsites for germination and recruitment seems crucial for P. canariensis regeneration, as shown in other pine species (de Groot et al 2004;Bonnet et al 2005;Vega et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the spatial pattern of soil resources at the scale of individual plants changes with successional status and disturbance (Robertson et al 1993;Gross et al 1995;Guo et al 2004;Mou et al 2005;Rodríguez et al 2009). Furthermore, these soil spatial patterns change at shorter time scales, such as within a single growing season, and in different ways for different soil variables (Wang et al 2007).…”
Section: Introductionmentioning
confidence: 99%